Implementing Lean Six Sigma throughout the Supply Chain - Cudney, Elizabeth; Kestle, Rodney (Productivity Press, 2018)
Explanations of theory, lists of rules, and discussions of procedure are the basis of learning the lean Six Sigma, however without a visceral understanding of the application of this powerful system in various circumstances the knowledge remains, at best, conjecture. Detailed examination of case studies that take real-world variables into account i.